Pengaruh Model Project Based Learning (PjBL) Terhadap Kreativitas Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMK Negeri 1 Laguboti Kabupaten Toba Tahun Pembelajaran 2023/2024 - Christin Febryana Pakpahan; Maringan Sinambela; Sabar Rudi Sitompul; Rida Gultom; Masniar Sitorus (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
This study aims to determine how much influence the Project Based Learning (PjBL) model has on the learning creativity of Christian Religious Education and Budi Pekerti class XI students of SMK Negeri 1 Laguboti Toba Regency for the 2023/2024 Learning Year, with the research hypothesis that there is a positive and significant influence of the Project Based Learning (PjBL) model on the learning creativity of Christian Religious Education and Budi Pekerti class XI students of SMK Negeri 1 Laguboti Toba Regency for the 2023/2024 Learning Year. The method used is an inferehential quantitative method with a population of all class XI students of SMK Negeri 1 Laguboti Toba Regency totaling 151 people with a sample of 60 people. Data were collected with a closed questionnaire of 30 items prepared by the author based on variable indicators according to expert theory. The questionnaire test was conducted on 40 students outside the research sample using 30 questionnaire items and after being tested the results of the validity of the questionnaire test were known to the value of rcount> table = 0.364-0.689> 0.312 and the reliability of the questionnaire test which was at a value of 0.866. has been tested for validity and reliability. The results of data analysis show that there is a positive and significant influence between the Project Based Learning (PjBL) model on the learning creativity of Christian Religious Education and Budi Pekerti class XI students of SMK Negeri 1 Laguboti Toba Regency Learning Year 2023/2024 with a coefficient of determination of 28.52% and a significant test of influence obtained Fcount>Ftabel of 24.649>4.00, meaning that H0 is rejected and Ha is accepted. This study suggests that in order for the Learning Creativity of Christian Religious Education and Budi Pekerti Class XI Students of SMK Negeri 1 Laguboti Toba Regency in a good class, the Project Based Learning (PjBL) Model by PAK teachers is implemented properly.